Factors associated with achilles tendon rupture in women`s collegiate gymnastics - Bonanno, J.; Cheng, J.; Tilley, D.; Abutalib, Z.; Casey, E. (Sports Health: A Multidisciplinary Approach, 2021)
Background: Achilles injury risk in women`s collegiate gymnastics is 10-fold higher than in all other collegiate sports. This study aims to identify risk factors for Achilles tendon ruptures in collegiate female gymnasts.